A SYNTACTIC ANALYSIS OF SIMPLE INTERROGATIVE SENTENCES IN THE HOUND OF THE BASKERVILLES BY SIR ARTHUR CONAN DOYLE - MUKHARAMAH, ANNIS MUFLIKHATUL (2010)
This research paper is aimed to give an analysis of simple interrogative sentences used in The Hound of the Baskervilles by Sir Arthur Conan Doyle. The objectives of this study are to know the various patterns and syntactic structure of simple interrogative sentence in The Hound of the Baskervilles by Sir Arthur Conan Doyle. The data are collected from The Hound of the Baskervilles by Sir Arthur Conan Doyle by using observation method; reading, selecting and collecting them. Then, the data are classified as interrogative sentences by referring to grammatical structure and analyzed based on Transformational Grammar approach, especially on syntactic analysis that are represented by the Chinese Box. The result of the data analysis, the writer finds the various patterns and syntactic structure of simple interrogative sentence. First, from 55 data, there are 24 data of Yes- no Questions and 31 data of Wh- Queation. And from 24 data of Yes-no Question: twenty one form of P + S + P of Yes- no Questions and three S + P + O/C form of Yes- no Questions. 31 data of Wh- Question, there are (1). three form of Subject : (S [who, what and which] + P + O) of Wh- Question, (2) six form of (Non-Subject: ( [7 wh] + S + P) Asking for P of Wh- Question, (3) twelve form of (Non- Subject: ( [7 wh] + S + P) Asking for O of Wh- Question, (4) three form of (Non-Subject: ( [7 wh] + S + P) Asking for C of Wh- Question, and (5) seven form of (Non- Subject: ( [7 wh] + S + P) Asking for Adjunct of Wh- Question. Second, and about syntactic structure, it can be concluded that from 55 data of simple interrogative sentences, there are 7 types of syntactic structure of simple interrogative sentences; (1) 4 sentences that have structure of: predication, modification, complementation and structure of coordination; (2) 14 sentences that have structure of: predication, modification and structure of complementation; (3) 9 sentences that have stucture of predication and structure of modification; (4) 19 sentences that have structure of predication and complementation; (5) 6 sentences that have structure of: predication, modification and structure of coordination; (6) 1 sentence that has structure of predication and structure of coordination; and (7) 2 sentences that have only structure of predication.